Comparative evaluation of bond strength and color stability of polyetheretherketone and zirconia layered with indirect composite before and after thermocycling: An in vitro study - Pooja Singh; Subhabrata Maiti; Amrutha Shenoy (Wolters Kluwer Medknow Publications, 2024)
Aim: This study investigates the interaction of zirconia and polyetheretherketone (PEEK) with indirect composite in fixed dental prostheses. This investigation aimed to assess the shear bond strength (SBS) and color stability of zirconia and PEEK before and after aging, addressing critical concerns in dental restorative applications. Settings and Design: The current in vitro study used 96 samples, 48 of which were divided into two groups, zirconia and PEEK, before and after thermocycling. A dual-axis chewing simulator was used for thermocycling. SBS was measured using a universal testing machine, and color stability was checked using a reflective spectrophotometer. Materials and Methods: Ninety-six samples were categorized into zirconia and PEEK groups, each with subgroups undergoing thermocycling. Samples were prepared using computer-aided design/computer-aided manufacturing milling and veneered with composite resin. Thermocycling involved 10,000 cycles, simulating stress levels equivalent to approximately 1 year of clinical use. SBS was assessed using standardized tests. Stereomicroscopic analysis was performed to evaluate the type of failure. Color stability of the core materials with indirect composite was done using a spectrophotometer before and after aging. Statistical Analysis Used: Statistical analysis included paired t-tests and independent t-tests in SPSS software. Results: The results revealed that SBS values for composite on PEEK decreased from 13.86 ± 0.164 MPa before thermocycling to 13.46 ± 0.185 MPa after thermocycling, with a significant difference (P < 0.005). However, both pre- and postthermocycling values for PEEK were higher than zirconia. The t-test confirmed the lower bond strength of composite to zirconia, with a noteworthy improvement after aging. Stereomicroscopic images revealed adhesive failure for the zirconia group and mixed (adhesive and cohesive) failure for the PEEK group. ΔE values were 3.21 ± 0.127 and 2.93 ± 0.142 for zirconia and PEEK groups, respectively (P < 0.005). Conclusion: Within the limitations of this study, it can be deduced that PEEK is a feasible substitute for zirconia when used in conjunction with indirect composite for the fabrication of dental prostheses.